THE COEFFICIENT OF PERFORMANCE OF THE FEMALE PLAYERS IN FUTSAL IN THE KURDISTAN REGION – IRAQ - ASAD, PROF DR. MAJEED KHUDAYKHSH; HUSSEIN, JAMEEL AHMAD (Journal of Duhok University, 2019)
The research aims to:- Putting an equation for effective performance during the matches, as an actual indicator to achieve the efficiency of the performance of female players in the Futsal in the Kurdistan Region of Iraq.- Setting standards and standards for the effective performance parameters of the female players of the futsal in the Kurdistan Region of Iraq.- The areas of researchHuman field: female players of the excellent class Futsal in the Kurdistan region of Iraq. Time domain: for the period from 11/10/2017 to 51/10/2018Sphere: Hall halls in clubs that are covered in the Kurdistan Region.The researchers used the descriptive approach and determined the research community of the female players of the Futsal in the clubs participating in the excellent league in the Kurdistan Region of Iraq. The sample of the research was chosen deliberately and the sample consisted of 76 players out of 118 with a percentage of 64.41% Of the eight clubs and machines:Zirvani, Kara and Aqra from Dohuk governorate, Erbil girl (two parts in Erbil and one in Sulaymaniyah), Jihan University of Erbil, Dervaza, and Aphrodite from Sulaymaniyah Governorate, Halabja from Halabja governorate.The statistical bag (spss-24 and Microsoft office excel-2016) was usedTo find statistical means arithmetical mean, standard deviation, kay square test, simple correlation coefficient (Pearson), the standard method in constant number method (relay method), torsion factor, percentage, T-test for independent samples.The researchers reached the following:- A special equation was established to measure the effective performance factor of the female players, futsal which is based on the success and failure of the basic skills, taking into account the time of participation of the player in the matches.- Setting standards and standards for the effective performance parameters of the female players of the Futsal in the Kurdistan Region of Iraq.